Needs Analysis for the Development of Problem-Posing Multimedia Package for Enhancing Students’ Understanding of Organic Chemistry Concepts: A Document Analysis - Tukur Ibrahim; Abdulmalik Sabitu; Nura Sani Usman (APS-TPI, 2026)
Background: This systematic needs analysis forms the foundational phase in developing a problem-posing multimedia package to improve senior secondary students' understanding of organic chemistry, specifically hydrocarbons. Grounded in a phenomenological approach, the study captures students' authentic learning challenges to ensure that the intended package addresses the real educational needs of the targeted students.Aims: The paper aims to identify and analyze prevalent student misconceptions in hydrocarbon concepts, providing diagnostic insights to guide the pedagogical design of the multimedia tool so it directly targets learning gaps.Methods: A qualitative approach was used with a purposive sample of ten chemistry students. Thematic analysis of students’ written documents (tests and exercises) was conducted to identify recurring errors and underlying misconceptions regarding hydrocarbon nomenclature, structure, and properties.Results: Six major error categories emerged: incorrect compound naming; misidentification of functional groups; poor understanding of isomerism; inappropriate hybridization assignment; erroneous carbon chain numbering; and inaccurate structure drawing. These reflect deeper conceptual gaps, such as difficulty recognizing parent chains, differentiating bonding types, identifying homologous series, and applying IUPAC rules consistently.Conclusion: The findings confirm that students' difficulties are systematic and conceptual, underscoring the necessity for a tailored instructional intervention. Developing a problem-posing multimedia package designed to explicitly address these identified challenges is essential for enhancing student comprehension and mastery of hydrocarbon concepts.